7 - L’expérience de la Communauté de l’Afrique de l’Est dans le contexte du plan d’action de Lagos - Ahmed MOHIDDIN (Africa Development, 1982)
The Lagos Plan of Action (LPA) calls for a far-reaching regional ap- proach to the socio-economic problems facing Africa. Collective self-reliance appears to be the accepted basis upon which these problems are to be solved. In this paper , the author is trying to provide a political analysis of the kinds of problems that, this approach , as a developmental one might be confronted with. He also makes additional suggestions as to how this approach can be made more efficient. He offers his analysis in terms of the historical experiences of one , now defunct , regional co-operative organization: the East African Community (EAC). It is the contention of his paper that the expe- riences of the EAC show that unless the basic roots of the problems to unity are removed , substantially modified or changed , the chances for success are very doubtful. In other words , unless the socio-economic ana political insti- tutions created during the colonial period , as well as the prevailing colonial capitalist ideology , are removed the possibilities for success of the LPA are very slim indeed. According to the author , the formula for success are the following two factors: Existence of an abundant political will at the leadership level Ideological compatibility, or at least the acceptance of disparate ideological co-existence. His analysis of the evolution of the Community which started from its historical roots to its demise shows that both factors were lacking in the case of the EAC. Kenya refused to give up her economic hegemony and ideologi- cal predisposition whereas Tanzania was determined to challenge that hege- mony and, in fact, to substitute her own ideological pre-disposition within the Community. In his concluding remarks, the author, drawing the lessons to be learnt from the EAC experience, suggests that the following factors should be considered very carefully: a) Regional groupings should consist of more than three states so as to a Regional groupings should consist of more than three states so as to minimize or diffuse the deleterious effects of competition amongst minimize or diffuse the deleterious effects of competition amongst the partner states. b) Regional groupings should restructure the inherited colonial institu- tions, otherwise the pull towards the former colonial metropoles would be too strong to resist. c) Since ideological incompatibilities cannot be avoided, educational measures should be taken to encourage tolerance, or at least a healthy understanding of these ideologies. Towards this end the establishment of regional institutions of higher learning - universities, technical and teacher training colleges, etc - would be extremely helpful. They would facilitate the training of future leaders with shared values, or at least with tolerant pre-dispositions. Ahmed MOHIDDIN, Professeur, Université de Nairobi - Nairobi, Kenya